Projeto jovem florestal: a semente em suas mãos - Costa, Daniela da [UNESP]; Villa, Lisandra Maraia [UNESP]; Valeri, Sérgio Valiengo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project Jovem Florestal minister environmental education classes with an emphasis on forest area, and practical activities related to reforestation, like production and maintenance of forest seedlings. The project has proved an important university extension instrument, giving to Jaboticabal and region through young students discussions about the importance of preserving the environment and improving quality of life and ethical vision of these young people. The classes are in the Experimental Nursery of Ornamental Plants and Forest of UNESP/FCAV, and students learn forestry practices and educational activities of trade and survival. The workload is 2 hours per week during the school period of the semester. The project also performs an important social work with people who have special needs, improving their quality of life,they became calmer especially because of the contact with nature and the educational recreational activities.

O projeto Jovem Florestal ministra aulas de educação ambiental com ênfase na área florestal, e nas atividades práticas relacionadas com o reflorestamento, como confecção e manutenção de mudas florestais. Ele têm-se revelado um importante instrumento de extensão universitária, levando para a população de Jaboticabal e região por meio de jovens aprendizes discussões sobre a importância da preservação do ambiente e melhorando a qualidade de vida, visão ética e educação desses jovens. As aulas são ministradas no Viveiro Experimental de Plantas Ornamentais e Florestais da UNESP/FCAV de Jaboticabal, e tem como conteúdo práticas florestais e atividades educativas com fins comerciais e de sobrevivência. A carga horária é de 2 horas semanais durante o período letivo do semestre. O projeto também realiza uma importante ação social com pessoas que possuem necessidades especiais, melhorando sua qualidade de vida, pois os mesmos apresentamse mais sociais e calmos, principalmente pelo contato que passam a ter com a natureza e realizando atividades recreativas educacionais.
Keywords: Environmental education; Educação ambiental